Study on buck evaluation based on semen quality and fertility (Bangladesh Journal of Animal Science, 2013)
The experiment was conducted to evaluate the performance of buck on the basis of semen quality and fertility. Data on 162 ejaculates from five adult Black Bengal bucks (B1, B2, B3, B4 and B5) were recorded. Individual buck effect was found to be significant on semen volume (p